Evaluasi Penerapan K3 Pada Proyek Pembangunan Pengaman Pantai Di Kecamatan Lease, Kabupaten Maluku Tengah - Delvia Rimesye Apalem (Hikamatzu | Journal of Multidisciplinary, 2024)
The process of building a construction project is an activity that has many potential hazards. Construction work is often a major contributor to high occupational accidents, due to the many incidents that harm various parties, especially the workforce involved. This study aims to analyze the application of occupational health and safety in the Coast Guard Construction Project, as well as to identify the relationship between factors that affect occupational safety and health. In addition, this study also aims to determine which factors are most influential on the application of occupational safety and health in coastal safety construction projects on Lease Island, Central Maluku Regency. The data analysis method used is multiple linear regression, with the aim of observing the relationship between variables and seeing the extent of the influence of the independent variable on the dependent variable, including productivity. Based on the results of research and analysis using the SPSS Version 26.00 program, it can be concluded that the application of OHS in the project needs to be implemented properly and followed up in the maintenance of work equipment. In addition, it is necessary to control the equipment periodically and prepare adequate supporting facilities so that it can be used in accordance with its function. The relationship between labor and productivity levels showed a value of r = 0.560, while the partial correlation between occupational safety and productivity levels obtained a value of r = 0.977. For occupational health and productivity levels, the correlation value is r = 0.550.